Preservice Elementary Teachers’ Perspectives about the Roles of Conceptual Understanding and Factual/Procedural Knowledge in Learning and Teaching Mathematics and Science - Sarah Quebec Fuentes; Mark Bloom; Heather Peace (Journal of Mathematics Education at Teachers College, 2014)
Preservice teachers often enter teacher education programs with naïve views about mathematics and science as well as the various domains of knowledge needed for effective teaching. A significant body of research has demonstrated that teacher knowledge is multifaceted and consists of both subject matter knowledge and pedagogical content knowledge. In this study, a cohort of preservice elementary teachers participated in an activity involving two components of subject matter knowledge (factual/procedural and conceptual). Analysis compares the preservice elementary teachers’ confidence in their understanding of and ability to teach factual/procedural and conceptual knowledge in mathematics and science. Qualitative analysis of a discussion following the activity provides insights into the quantitative findings.